Stages and Determinants of E-Government Development: A Twelve-Year Longitudinal Study of Global Cities. Issue 6 (5th December 2020) - Ingrams, Alex; Manoharan, Aroon; Schmidthuber, Lisa; Holzer, Marc
ABSTRACT: Global e-government innovations are at the forefront of municipal efforts to be better organized and more efficient in delivering services and improving outcomes for the public. Scholars have argued that such innovations are embedded in institutional and environmental factors, and municipal e-government growth evolves through stages as a result of the effects of these factors. However, existing studies rarely model the distinct success factors of the different stages. This article addresses that shortcoming with data from the largest cities in the world's top 100 "most wired" countries from 2003 to 2016. Cluster analysis addresses whether there are any consistent growth trends, and finds that there are four clusters of e-government development. Regression analysis tests whether stages may be driven by specific factors, and findings reveal that e-government stages mostly have uniform drivers. Population size, GDP, and regional competition have a positive association across all stages. However, democracy level appears to have a more ambiguous status, as it influences some higher stages in large countries but has a negative association in small countries.